Pembinaan Pegawai Bagian Management Trainee di PT Jasa Marga Pusat Jakarta Timur - Rayssa Nardina Shalsabila; Sari Ningsih (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2023)
This study aims to determine what kind of coaching in Management Trainee of PT Jasa Marga Headquarter East Jakarta. This study using descriptive qualitative method. To determine what kind of coaching in Management Trainee Department of PT Jasa Marga Headquarter East Jakarta, researcher uses few of data collecting technique which are observing, interview, and documentation studies. As of data analysis technique uses the following steps: data reduction, data presentation, and conclusion. The results of this study show that the coaching based that the coaching based on participation and performance are quite effective. The supporting factor of the employee coaching in Management Trainee Department is technology development in daily performance. The inhibiting factors of the employee coaching is number of employee who got decreased.